Emotion-Driven Consumption in Digital Retail: A Review of ‎Women’s Online Shopping Experience - MS , Pallavi; Gonela, Dr. Saradhi; Dikkatwar, Dr. Ramkrishna (International Journal of Accounting and Economics Studies, 2025)
The growth rates of e-commerce and social commerce have significantly changed consumers, ‎especially women, who frequently engage in online shopping not only for transactions but also as ‎an emotional or metaphorical experience. This review addresses the psychological complexity of ‎shopping online, which includes emotional stimuli and psychological consequences experienced ‎by women. Based on the 2014-2024 research investigations, the review combines the results of the ‎literature on the issue of impulse purchase, online shopping addiction, hedonic motivation, and ‎emotional well-being. It reveals some of the major emotional triggers, including aesthetics, ‎personalized advertising, social media, and the dopamine reward system. It results in positive ‎psychological effects, such as making people feel good and relieving stress, and negative results, ‎later known as buyer's remorse, and ultimately leads to buying more. Moderating factors, digital ‎literacy, social support, and coping strategies are also analyzed during the study. Niche areas of ‎research gaps are recognized as spheres of intersectionality, chronic effects, and culturally diverse ‎outlooks. The review concludes with a focus on the necessity of targeted interventions and ‎educational policies to promote healthier online consumer behavior‎.